Arsenic Trioxide Exerts Anti-lung Cancer Activity by Inhibiting Angiogenesis - Yang, Meng-Hang; Zang, Yuan-Sheng; Huang, Hai; Chen, Kun; Li, Bing; Sun, Guang-Yuan; Zhao, Xue-Wei (Current Cancer Drug Targets, 2014)
Arsenic trioxide (As2O3) has been used in the clinic for the treatment of acute promyelocytic 1eukemia and some solid tumors. However, its effectiveness against lung cancer has not been well demonstrated, and the underlying mechanism(s) of action remain unclear. In the present study, we found that As2O3 significantly inhibited the growth of non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) xenograft tumors. It was observed to have antiangiogenic effects in xenograft models and matrigel pellets. It also significantly inhibited the expression of VEGF-A, VEGFR-2, HIF-1α, Dll4 and Notch-1 in vivo. Moreover, As2O3 also inhibited the expression of HIF-1α, VEGFR-2, Dll4, and Notch-1 in lung cancer cell lines and human umbilical vein endothelial cells. These findings suggest that As2O3 has significant anti-lung cancer activity, which may occur as a result of the antiangiogenic effects caused by the downregulation of the VEGF and Dll4-Notch signaling pathways
Keywords: Dll4